2018
DOI: 10.1152/japplphysiol.00383.2018
|View full text |Cite
|
Sign up to set email alerts
|

Repeated exposure to heat stress induces mitochondrial adaptation in human skeletal muscle

Abstract: The heat stress response is associated with several beneficial adaptations that promote cell health and survival. Specifically, in vitro and animal investigations suggest that repeated exposures to a mild heat stress (~40°C) elicits positive mitochondrial adaptations in skeletal muscle comparable to those observed with exercise. To assess whether such adaptations translate to human skeletal muscle, we produced local, deep tissue heating of the vastus lateralis via pulsed shortwave diathermy in 20 men (n=10) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
68
8
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(79 citation statements)
references
References 37 publications
2
68
8
1
Order By: Relevance
“…However, our findings differ from work reporting repressed expression of PGC-1α mRNA expression, or no change in mitochondrial density following acute ( Petrie et al, 2016 ) and longer term heat therapy, respectively ( Hesketh et al, 2019 ). Instead, our findings in general corroborate with data acquired in cell and rodent models showing an increase in markers associated with mitochondrial biogenesis ( Liu and Brooks, 2012 ; Tamura and Hatta, 2017 ), which have been extended to human models demonstrating a HSP-associated increase mitochondrial adaptation in healthy weight-bearing as well as immobilized humans ( Hafen et al, 2018 , 2019 ). We did not observe increased PGC-1α mRNA levels in the current study, despite the increase in gene transcription coding for mitochondria-related proteins.…”
Section: Discussionsupporting
confidence: 90%
“…However, our findings differ from work reporting repressed expression of PGC-1α mRNA expression, or no change in mitochondrial density following acute ( Petrie et al, 2016 ) and longer term heat therapy, respectively ( Hesketh et al, 2019 ). Instead, our findings in general corroborate with data acquired in cell and rodent models showing an increase in markers associated with mitochondrial biogenesis ( Liu and Brooks, 2012 ; Tamura and Hatta, 2017 ), which have been extended to human models demonstrating a HSP-associated increase mitochondrial adaptation in healthy weight-bearing as well as immobilized humans ( Hafen et al, 2018 , 2019 ). We did not observe increased PGC-1α mRNA levels in the current study, despite the increase in gene transcription coding for mitochondria-related proteins.…”
Section: Discussionsupporting
confidence: 90%
“…Many, if not all , studies have revealed that heat stress and/or vigorous muscle contraction result in the upregulation of HPS70 in fast-and slow-twitch muscles from mammals (Oishi et al 2002;Tupling et al 2007;Tamura et al 2015;Hafen et al 2018). Conversely, the current study showed that neither thermal treatment nor fatiguing stimulation elicited changes in the expression of HSP70 (Fig.…”
Section: Discussioncontrasting
confidence: 61%
“…; Hafen et al. ). Conversely, the current study showed that neither thermal treatment nor fatiguing stimulation elicited changes in the expression of HSP70 (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations